Prevalência de anticorpos Anti-Neospora caninum em rebanhos caprinos das regiões Central e Oeste do Rio Grande do Norte - Fonseca, Zuliete Aliona Araujo de Souza (Universidade Federal Rural do Semi-Árido, 2012)
The neosporosis is a disease caused by protozoan Neospora caninum, which has wide range of hosts, it promoting reproductive and neurological changes. Presents in its life cycle, intermediate hosts between they are the goats, and definitive hosts represented by the canids. The study was conducted in the state of Rio Grande do Norte in partnership with Brazilian Company of Agricultural Research. Were visited and surveyed two Mesoregions producing (Central and West), with aim of perform epidemiological study of antibodies anti-N. caninum, questionnaires were applied to characterization zoosanitary, beyond of blood collection to obtain serum. The sera were stored at -20°C until analysis at Embrapa Beef Cattle. Serum samples were subjected to indirect immunofluorescence (IFAT ≥ 1:50) and evaluated using univariate and multivariate analysis for verification of risk factors. The serological results demonstrated high presence of antibodies anti-N. caninum, with prevalence of 36.5% ranging from zero to 100% between the properties studied. Among the risk factors, the system of creation presented a highest correlation with the agent, followed by water source and presence of wild dogs in the facilities, directly influencing the presence of protozoan in goat herd of Rio Grande do Norte
Prevalence of anti-Neospora caninum antibodies in goat herd of the Central Region and West of Rio Grande do Norte
Keywords: Protozoan; Neosporosis; Abortion; Risk factors; Protozoário; Neosporose; Aborto; Fatores de risco; CIENCIAS AGRARIAS::MEDICINA VETERINARIA